Preparation and antitubercular activity of lipophilic diamines and amino alcohols - Celso OR Júnior; Mireille Le Hyaric; Cristiane F da Costa; Taís A Corrêa; Aline F Taveira; Débora P Araújo; Elaine FC Reis; Maria Cristina S Lourenço; Felipe RC Vicente; Mauro V de Almeida (Memorias do Instituto Oswaldo Cruz, 2009)
A series of diamines and amino alcohols derived from 1-dodecanol, 1-tetradecanol, 1,2-dodecanediol and 1,2-tetradecanediol were synthesized and tested for their antitubercular activity. Compounds 3, 8 and 9 were found to be the most active (MIC of 6.25 ¼g/mL). Nine other compounds displayed activity against Mycobacterium tuberculosis, with a MIC of 12.5 ¼g/mL.